Effects of rapid thermal processing on chemically deposited antimony sulfide thin films. (15th June 2018) - Vinayakumar, V.; Hernández, C.R. Obregón; Shaji, S.; Avellaneda, D.A.; Martinez, J.A. Aguilar; Krishnan, B.
Abstract: In this paper, we report studies on rapid thermal processed (RTP) antimony sulfide (Sb2 S3 ) thin films grown on glass and Mo-coated glass substrates by chemical bath deposition. Structure, morphology, elemental composition, optical and electrical properties of the thin films processed at different temperatures (325–700 °C) for 1–5 min were evaluated. X-ray diffractometry and Raman spectral studies showed the crystalline nature of the thin films. XPS analysis demonstrated the elemental composition and chemical states. Optical band gap of the films was evaluated from the optical absorption spectra, and the bandgap values were in the range of 1.7–2.1 eV. All the RTP samples showed photocurrent response. Crystallinity and morphology of the films were modified by varying RTP temperature and time. Graphical abstract: Highlights: Chemically deposited Sb2 S3 thin films and their Rapid Thermal processing. Transformation of amorphous to polycrystalline by RTP at 625–700 °C for 1–5 min in Sb2 S3 /Glass. Fast crystallization at low temperature for Sb2 S3 thin films on Mo/Glass. Improved photophysical properties for Sb2 S3 by RTP.